Robust image hashing via colour vector angles and discrete wavelet transform. Issue 3 (1st March 2014) - Tang, Zhenjun; Dai, Yumin; Zhang, Xianquan; Huang, Liyan; Yang, Fan
Abstract : Colour vector angle has been widely used in edge detection and image retrieval, but its investigation in image hashing is still limited. In this study, the authors investigate the use of colour vector angle in image hashing and propose a robust hashing algorithm combining colour vector angles with discrete wavelet transform (DWT). Specifically, the input image is firstly resized to a normalised size by bi‐cubic interpolation and blurred by a Gaussian low‐pass filter. Colour vector angles are then calculated and divided into non‐overlapping blocks. Next, block means of colour vector angles are extracted to form a feature matrix, which is further compressed by DWT. Image hash is finally formed by those DWT coefficients in the LL sub‐band. Experiments show that the proposed hashing is robust against normal digital operations, such as JPEG compression, watermarking embedding and rotation within 5°. Receiver operating characteristics curve comparisons are conducted and the results show that the proposed hashing is better than some well‐known algorithms.